Coating with chitosan film of sea bream (Sparus aurata) fillets: determining shelf life in refrigerator conditions - İZCİ,Levent (2018)
Abstract In the investigate, we objectived to assess the effect of coating with chitosan film on the shelf life. To this end, skinless sea bream fillets were separated as control group (C), vacuum packed (VP) and coated with chitosan film and vacuum packed (CF+VP). Samples of each group were periodically analyzed for microbiological [Total mesophilic aerobic count (TMAc) and Total psychrophilic aerobic count (TPAc)] and physicochemical [pH, Total volatile basic nitrogen (TVB-N), Thiobarbituric acid (TBA) and Trimethylamine nitrogen (TMA-N)] in storage time. It was determined that CF+VP had the highest shelf life among the sample groups. The findings of the study showed that covering sea bream fillets with chitosan film and vacuum packaging significantly prolongs the consumption of the sea bream fillets.